The Demikernel Datapath OS Architecture for Microsecond-scale Datacenter Systems - Zhang, Irene; Raybuck, Amanda; Patel, Pratyush; Olynykr, Kirk; Nelson, Jacob; Leija, Omar S. Navarro; Martinez, Ashlie; Liu, Jing; Anna Kornfeld Simpson; Jayakar, Sujay; Penna, Pedro Henrique; Demoulin, Max; et al. (Symposium on Operating Systems Principles (SOSP '21), 2021)
Datacenter systems and I/O devices now run at single-digit microsecond latencies, requiring ns-scale operating systems. Traditional kernel-based operating systems impose an unaffordable overhead, so recent kernel-bypass OSes [73] and libraries [23] eliminate the OS kernel from the I/O datapath. However, none of these systems offer a general-purpose datapath OS replacement that meet the needs of µs-scale systems. This paper proposes Demikernel, a flexible datapath OS and architecture designed for heterogenous kernel-bypass devices and µs-scale datacenter systems. We build two prototype Demikernel OSes and show that minimal effort is needed to port existing µs-scale systems. Once ported, Demikernel lets applications run across heterogenous kernel-bypass devices with ns-scale overheads and no code changes.